Profitability and Determinants of System of Rice Intensification Technology Usage among Rice Farmers - Akanbi , Sheu-Usman Oladipo; Mukaila, Ridwan; Ojimiwe, Osasa Kehinde; Olohungbebe, Sheu Ahmad; Fidelis, Emeka Solomon (Jordan Journal of Agricultural Sciences, 2025)
In Nigeria, rice is the main component of the food bowl and a staple crop. The majority of the nation’s rice is produced using traditional methods. This method has driven up the price of producing rice and made it more difficult for farmers to reach their full output capacity. Due to these, the rice intensification system (SRI) was created in the rice-growing industry. However, research on the financial viability of SRI technology and the variables affecting farmers’ use of it in Nigeria is lacking. Therefore, this study investigated the profitability and determinants of the system of rice intensification technology usage among rice farmers. A questionnaire was used to collect information from 180 rice farmers using SRI technology. Descriptive statistics, profitability analysis, and multivariate logistic regression were employed in the analysis of the data. The study discovered that the majority of the rice farmers using SRI technology in Nigeria were economically active males. They made a gross margin of USD 370.55, a benefit-cost ratio of 1.68, and a profitability ratio of 0.41 per hectare; indicating that the use of SRI technology in rice farming is profitable. The result of the multivariate analysis of the determinants of the use of SRI revealed that the availability of extension services, farming experience, association membership, household size, and education influenced the use of different SRI technologies. The study recommends the promotion of SRI through knowledge exchange, extension demonstrations, and farmers’ participation in training programs.